The theory of monetary disorder: Debt finance, existing assets, and the consequences of prolonged monetized budget deficits and ultra-easy monetary policy - Thomas Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
This paper introduces the notion of monetary disorder. The underlying theory rests on a twin circuits view of the macro economy. The idea of monetary disorder has relevance for understanding the experience and consequences of the recent decade-long period of monetized large budget deficits and ultra-easy monetary policy. Current policy rests on Keynesian logic whereby a large fall in aggregate demand warrants robust offsetting monetary and fiscal policy actions. That logic neglects potential monetary disorder being bred within the financial circuit in the form of inflated asset prices and leveraged balance sheets. That disorder is likely to develop long before inflation accelerates so that inflation targeting fails to protect against it. Political factors increase the policy danger as the benefits of disorder are front-loaded and the costs backloaded. The paper concludes with a policy discussion regarding how to prevent Keynesian goods market counter-cyclical stabilization policy from causing monetary disorder.
Keywords: E00; E12; E30; E40; E63; 330; Monetary disorder; twin circuits; inflation; asset price bubbles; budget deficits; modern money theory (MMT)